Otras formas de inmigración en la novela costarricense contemporánea: Rima de Vallbona y Virgilio Mora - Chen Sham, Jorge (2012)
The article discusses the repercussions of immigration in terms of the perceptions and or representations of the space that the immigrants must now reconstruct after having left the home and community which provided to them their identity and relevancy. Immigration puts off center the individual and makes him or her confront an ontological and cultural exile, when immigration occurs for reasons other than economic ones. The two Costa Rican novels in this study, World, Demon and Woman (Rhyme of Vallbona, 1991) and Memories of a Psychiatrist (Virgilio Mora, 2005), allow us to analyze other forms of immigration, respectively, because of the regrouping of the familiar nucleus or specialization of studies. These two forms are bound to that exile in such a way that it preoccupies and marks the immigrants.